Televisões universitárias público-estatais no interior do Brasil: um breve eco da pluralidade rumo à digitalização - Prevedello, Carine Felkl (Universidade do Vale do Rio dos Sinos, 2013)
Celebrating 70 years of existence in Brazil, open television, covering almost the totality of Brazilian homes, will enter the phase of digital broadcasting. This change in paradigm – anchored by the superficial public discussion and sustained by researches financed by market interests – could mean an inversion in the genuine dichotomy of television in the country, which maintains the commercial broadcasters in open channels, in opposition to public access channels available on cable TV. Televisions related to universities, inserted in the field of public access channels, gave birth to a representative segment in the country, which, along with community TV stations and educational ones, would consist in a center that is able to foment the production of local content, contributing to the plurality in the offer of audiovisual products and, consequently, to the democratization of communication in Brazil. By identifying this potentiality in broadcasters related to federal, state or regional universities, associating to these institutions the character of public financing and goal that produce local or regional content aligned to audiovisual plurality and democratization, this thesis proposes an investigation on public state university televisions in inland cities of Brazil. The evaluation of the preparation to digital convergence in eight stations public state university televisions in inland cities of Brazil confirms the technical limitation that characterizes this sector in the country, the difficulties in financing, the scarce insertion in the political debate on technological change that reaches the Brazilian audiovisual spectrum and the timid experiences related to interactivity. This research confirms, on the other hand, the direct association of this group to the priority of local content, identifying the profile of institutional promotion and rare cases of advanced scenarios towards digitization in a field marked by experimentation and lack of investment. However, the concrete horizon to amplify the space of televisions, either the ones related to universities or the more general group of public state broadcasters in the new paradigm of digital television in Brazil, remains hostage of political definitions that do not present perspectives to reverse the current dichotomy present in the analogical phase.
Keywords: Televisões universitárias; Digitalização; Democratização; University televisions; Digitization; Democratization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação